2006
DOI: 10.1097/01.shk.0000192126.33823.87
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a devastating intra-abdominal emergency in the newborn period. The disease involves bowel wall inflammation, ischemic necrosis, eventual perforation, and the need for urgent surgical intervention. Unrecognized or left untreated, the neonate can decompensate quickly, often progressing to shock, multisystem organ failure, and eventual death. During the past several years, a number of basic science and clinical trials have been established in an attempt to understand the pathoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 104 publications
1
119
2
Order By: Relevance
“…In our current model, the omission of anti-inflammatory cytokines provides a worst-case scenario with respect to the harmful effects of the inflammatory response. The qualitative relationships established in this study that indicate both beneficial and harmful effects of probiotics are still expected to hold in the presence of cytokines, but additional insight into the interplay of the immune response and probiotic treatment will require future modeling of cytokine populations [40,41].…”
Section: Additional Considerations and Conclusionmentioning
confidence: 99%
“…In our current model, the omission of anti-inflammatory cytokines provides a worst-case scenario with respect to the harmful effects of the inflammatory response. The qualitative relationships established in this study that indicate both beneficial and harmful effects of probiotics are still expected to hold in the presence of cytokines, but additional insight into the interplay of the immune response and probiotic treatment will require future modeling of cytokine populations [40,41].…”
Section: Additional Considerations and Conclusionmentioning
confidence: 99%
“…Several pro-inflammatory cytokines that mediate inflammatory cell recruitment through activation and amplification of the immune response in local host defense have been implicated in NEC including TNF-α, IL-1β, IL-6, IL-8, IL-12, and IL-18 [99][100][101] . Antiinflammatory cytokines modulate the host's inflammatory response and if they fail to achieve their goal, proinflammatory mediators can continue, resulting in tissue injury [4] .…”
Section: Cytokinesmentioning
confidence: 99%
“…Therefore, its delayed occurrence after birth, its rapid onset, highly fulminant nature, and progression to death, as well as its severe morbidity, require identification of prospective new biomarkers specific for high NEC risk (Young et al 2009). Some studies have suggested the efficacy of several inflammatory mediators such as C-reactive protein (CRP), interleukin-6 (IL-6) and serum amyloid A (SAA) measurements in the diagnosis of NEC (Pourcyrous et al 2005;Hallstrom et al 2006;Markel et al 2006;Evennett et al 2009;Cetinkaya et al 2010). These all have difficulties that limit their use.…”
mentioning
confidence: 99%